2005
DOI: 10.1097/00000542-200508000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against Trigger Point Injection Technique for the Treatment of Cervicothoracic Myofascial Pain with Botulinum Toxin Type A

Abstract: Injection of BoNT-A directly into trigger points did not improve cervicothoracic myofascial pain. The role of direct injection of trigger points with BoNT-A is discussed in comparison to other injection methodologies in the potential genesis of pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 28 publications
3
122
2
1
Order By: Relevance
“…Botulinum toxin is on option for patients with refractory, highly symptomatic myofascial pain. However, the evidence is unconvincingly either for or against benefit [16][17][18][19] (NCCN Category 3). The associated expense, questionable benefit, and difficulty in obtaining coverage for botulinum toxin, makes this option unfeasible for many patients.…”
Section: Common Rehabilitation Problems and Their Treatment Myofasciamentioning
confidence: 99%
“…Botulinum toxin is on option for patients with refractory, highly symptomatic myofascial pain. However, the evidence is unconvincingly either for or against benefit [16][17][18][19] (NCCN Category 3). The associated expense, questionable benefit, and difficulty in obtaining coverage for botulinum toxin, makes this option unfeasible for many patients.…”
Section: Common Rehabilitation Problems and Their Treatment Myofasciamentioning
confidence: 99%
“…Its conclusion merely implies that a fi xed dosage design does not work for Gobel et al's ( 2006 ) protocol. The study of Ferrante et al ( 2005 ), comparable in size to Gobel's study (large number of patients) sheds negative light on the effi cacy of BoNT (in this case onaA) in MPS. It is fundamentally different from Gobel's study since investigators injected only a limited number of trigger points (no more than fi ve).…”
Section: Commentmentioning
confidence: 84%
“…Other negative studies have found BoNT effi cacy statistically similar to placebo, but, in these studies, both BoNT and placebo alleviated pain signifi cantly compared to baseline pain (Wheeler et al 1998 ;Ferrante et al 2005 ;Querma et al 2006). As emphasized by Gerwin ( 2014 ), in this scenario, the only possible conclusion is that the study showed a large placebo effect precluding proper assessment of BoNT effi cacy.…”
Section: Commentmentioning
confidence: 92%
See 1 more Smart Citation
“…Ferrante et al compared the effects of TPI and a placebo and reported no statistically significant difference 18) . Ga et al compared the effects of intramuscular stimulation (IMS) and TPI, and reported that the former was better at alleviating pain and increasing the range of motion in the neck joint 19) .…”
Section: Discussionmentioning
confidence: 99%